Effects of media stories featuring coping with suicidal crises on psychiatric patients: Randomized controlled trial. Issue 1 (4th November 2021) - Niederkrotenthaler, T.; Baumgartner, J.; Kautzky, A.; Fellinger, M.; Jahn, R.; Wippel, A.; Koch, M.; König-Castillo, D.; Höflich, A.; Slamanig, R.; Topitz, A.; Wancata, J.; et al.
Abstract: Background: Accumulating evidence suggests beneficial effects of media stories featuring individuals mastering their suicidal crises, but effects have not been assessed for psychiatric patients. Methods: We randomized n = 172 adult psychiatric patients ( n = 172, 97.1% inpatients) to read an educative article featuring a person mastering a suicidal crisis ( n = 92) or an unrelated article ( n = 80) in a single-blind randomized controlled trial. Questionnaire data were collected before ( T 1 ) and after exposure ( T 2 ) as well as 1 week later (study end-point, T 3 ). The primary outcome was suicidal ideation as assessed with the Reasons for Living Inventory; secondary outcomes were help-seeking intentions, mood, hopelessness, and stigmatization. Differences between patients with affective versus other diagnoses were explored based on interaction tests. Results: We found that patients with affective disorders ( n = 99) experienced a small-sized reduction of suicidal ideation at 1-week follow up (mean difference to control group [MD] at T 3 = −0.17 [95% CI −0.33, −0.03], d = −0.15), whereas patients with nonaffective diagnoses ( n = 73) experienced a small-sized increase ( T 2 : MD = 0.24 [95% CI 0.06, 0.42], d = 0.19). Intervention group participants further experienced a nonsustained increase of help-seeking intentions ( T 2 : MD = 0.53 [95% CI 0.11, 0.95], d = 0.19) and a nonsustained deterioration of mood ( T 2 : MD = −0.14 [95% CI −0.27, −0.02], d = −0.17). Conclusions: This study suggests that patients with affective disorders appear to benefit from media materials featuring mastery of suicidal crises. More research is needed to better understand which patient groups are at possible risk of unintended effects.